2003
DOI: 10.1002/dvdy.10250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed during Xenopus laevis limb regeneration by using subtractive hybridization

Abstract: Suppression polymerase chain reaction-based subtractive hybridization was used to identify genes that are expressed during Xenopus laevis hindlimb regeneration. Subtractions were done by using RNAs extracted from the regeneration-competent stage (stage 53) and regeneration-incompetent stage (stage 59) of limb development. Forward and reverse subtractions were done between stage 53 7-day blastema and stage 53 contralateral limb (competent stage), stage 59 7-day pseudoblastema and stage 59 contralateral limb (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…Most of these genes fell into the categories of metabolism, cell physiological process, cell cycle regulation, and protein synthesis and transport. Subtractive hybridization was also used to compare transcript expression after amputation at a regeneration‐competent versus a regeneration‐deficient stage of Xenopus limb bud development (King et al., 2003). This study identified three categories of cDNA clones: clones expressed at both competent and deficient blastemas, clones with highest expression in regeneration‐competent blastemas, and clones with highest expression in regeneration‐deficient blastemas.…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…Most of these genes fell into the categories of metabolism, cell physiological process, cell cycle regulation, and protein synthesis and transport. Subtractive hybridization was also used to compare transcript expression after amputation at a regeneration‐competent versus a regeneration‐deficient stage of Xenopus limb bud development (King et al., 2003). This study identified three categories of cDNA clones: clones expressed at both competent and deficient blastemas, clones with highest expression in regeneration‐competent blastemas, and clones with highest expression in regeneration‐deficient blastemas.…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%
“…Subtractive hybridization was also used by King et al (2003) to identify regeneration specific genes in the hindlimb bud. By subtracting combinations of cDNA obtained from competent (st. 53) vs. incompetent (st. 59) 7 day blastemas, or control, unoperated limbs at the same stage, they identified genes that were preferentially expressed in regenerating limbs, nonregenerating limbs, or both, relative to uncut limbs.…”
Section: Est Approachesmentioning
confidence: 99%
“…A full-length cDNA was subsequently isolated from a Xenopus stage 17 neurula whole-embryo cDNA library (King et al, 2003). The cDNA was sequenced and characterized and shown to be most highly homologous to MMP-28 (Fig.…”
Section: Isolation and Sequencing Of Full-length Xenopus Mmp-28 (Xmmpmentioning
confidence: 99%
“…As the original identification of XMMP-28 was as an up-regulated transcript in 7-day postamputation pseudoblastemas from regeneration incompetent stage 59 hindlimbs (King et al, 2003), it was of interest to determine whether XMMP-28 expression was altered during functional regeneration. Hindlimbs of regeneration competent stage 53 Xenopus laevis were amputated at the level of the prospective tibia/fibula to examine expression of XMMP-28 during blastema formation and the events leading to limb regeneration (Dent, 1962).…”
Section: Xmmp-28 Expression In Regenerating Limbsmentioning
confidence: 99%
See 1 more Smart Citation